100‐kyr Paced Climate Change in the Pliocene Warm Period, Southwest Pacific. Issue 4 (17th April 2019) - Caballero‐Gill, R. P.; Herbert, T. D.; Dowsett, H. J.
Abstract: The mid to late Pliocene ( 4.2–2.8 Ma.) represents an experiment in climate sensitivity to orbital pacing in which nearly all continental ice was confined to the Southern Hemisphere. Most studies have emphasized the dominant role of obliquity in determining changes in ice volume and temperature at this time, although most records come from the Northern Hemisphere, instead of the hemisphere where the bulk of ice resided. We present the first orbitally‐resolved, mid to late Pliocene Southern Hemisphere paired records of surface and subsurface variability from two deep ocean archives from the Southwest Pacific Ocean (Sites 594 and 1125). These records indicate dominance of low frequencies centered at 100 kyr for this time period. Because these signatures extend coherently and synchronously from middepth water properties (δ 13 C, δ 18 O of benthic foraminifera), which have their chemistry set in the subantarctic belt, to the surface (alkenone‐derived surface temperature estimates, color reflectance, and magnetic susceptibility), we infer that the fingerprint of the 100‐kyr cycles must have extended over a large region of the Southern Hemisphere. We propose that nonlinearities in climate response to precessional forcing—most likely through ice sheet and/or carbon cycle behavior—generated the observed low frequency. A review of published mid to late Pliocene time series suggests that the 100‐kyr pacing may be a widespread phenomenon and that major approximately 100‐kyr excursions in Pliocene climate were an important overlay to the underlying 41‐kyr glacial‐interglacial rhythm. These results caution against uncritical use of existing Pliocene isotopic templates to construct high‐resolution age models. Plain Language Summary: We recreated a detailed account of surface and subsurface ocean change at two locations within the Southern Hemisphere in the middle to late Pliocene Epoch ( 4.2–2.8 Ma) using data obtained from deep‐ocean sediment cores. Our work showed that all variables measured (each representing a response from different parts of the climate system) fluctuated synchronously through time at specific rhythms and one of which, at approximately 100 kyr, was surprising to find. We found that the pervasive nature of this rhythm at 100 kyr in our reconstructions is also found in other data sets connected to the Antarctic region. First, we propose that approximately 100‐kyr excursions in Pliocene climate are an important component in the overall pacing of glacial to interglacial times in the Pliocene. Such large excursions in climate would require powerful nonlinear feedbacks to forcing from the Earth's orbital precession cycle, likely involving ice sheet or carbon cycle dynamics. Second, we suggest that current global benthic isotope stacks (taken as an average representation of deep ocean temperature and ice volume changes on Earth) may not be fully representative of climate variability in some intervals of the Pliocene and therefore must be used carefully if used as a means to convert depth to time. Key Points: New, high‐resolution, paired surface‐subsurface paleoclimate reconstructions from the Southern Hemisphere, mid to late Pliocene Epoch Dominance of low frequencies centered at 100 kyr, extending coherently and synchronously from middepth water properties to the surface Low‐frequency dominance in power spectra likely related to underlying sensitivity to precessional forcing, requiring nonlinear amplifiers